Avaliação da qualidade da carne-de-sol produzida e comercializada em municípios do Rio Grande do Norte - Gurgel, Teresa Emanuelle Pinheiro (Universidade Federal Rural do Semi-Árido, 2010)
It evaluated the quality of carne-de-sol in the period from June to September of 2010 sold in five cities of Rio Grande do Norte - Mossoró, Apodi, Areia Branca, Baraúna and Grossos. It was collect 80 samples of carne-de-sol, of which 44 were from small establishments and 36 purchased in supermarkets and stores. The samples were subjected to microbiological testing - Salmonella, determining the most probable number of fecal coliform, halophilic bacteria and Staphylococcus aureus, the samples were positive for this bacteria were analyzed for resistance to antibiotics, and physical-chemical properties (pH, water activity, minerals and humidity). There was an interaction between intrinsic pH value (μ = 5.702) and Aa (μ = 0.868), , indicating a favorable environment for their multiplication, resulting in values that stood out significantly in what is expected legislation counting S. aureus (μ = 4.81 log UFC at 78.75%), Salmonella (25%) and fecal coliform (μ = 2.36 LogNMP / g, 63.75%). A significant correlation (p <0.05) between the number of halophilic bacteria (μ = 4.87 log UFC) and S. aureus, such conditions may be used as an indicator of contamination in the sun-dried meat. To the antibiotics, 22.5% of strains were resistant to gentamicin, whereas for penicillin G, chloramphenicol, tetraciclina were 100%, 67.5% and 46.26% respectively. It was found that the meat produced and marketed in the sun studied region is improper (96.25%) for consumption in accordance with Brazilian law
Quality evaluation of carne-de-sol produced and sold in the cities of Rio Grande do Norte
Keywords: Salmonella; Sanitary conditions; S. aureus; halophilic bacteria; sensitivity to antibiotics; Salmonella; Condições sanitárias; S. aureus; bactérias halofílicas; resistência à antibióticos.; CIENCIAS AGRARIAS::MEDICINA VETERINARIA